Understanding Partiality in pro‐Drop Languages: An Information‐Structure Approach. (22nd July 2019) - Frascarelli, Mara; Jiménez‐Fernández, Ángel L.
Abstract: This article explores the acceptability and interpretation of referential null subjects in several varieties of Spanish (both Peninsular and American varieties) in different syntactic contexts (matrix and embedded) and distinct clause types (under bridge verbs, under factive verbs, and in adverbial clauses). Based on the results of an original online survey, completed by almost 300 respondents all over the world, it is shown that, in contrast with a consistent‐ pro ‐drop language like Italian, some Spanish varieties exhibit partial‐ pro ‐drop properties; this contributes to a recent line of research dealing with partiality in consistent‐ pro ‐drop languages. We argue that such variation can be accounted for within an information‐structure approach, in which the Topic Criterion (Frascarelli 2007), the formation of topic chains, and the existence of silent topics play a crucial role. Degrees of partiality are attributed to an interface condition that combines information‐structure requirements with PF visibility of overt copies in topic chains. Partial‐ pro ‐drop properties can then be explained by reference to independent syntactic conditions, such as the preference for overt minimal links and the sensitivity to islands.